JURIDICAL ANALYSIS OF JUDGES' DECISIONS ON DIVORCE CIVIL SERVANTS WITHOUT PERMISSION FROM THE SUPERIOR - Dumaria Evi Mawartiku Palamarta Br. Gultom; Rosnidar Sembiring; Yefrizawati Yefrizawati; Afnila Afnila (Green Publisher, 2023)
Divorce is the release of the marriage bond or the dissolution of the marriage relationship. Law No. 1 of 1974 concerning Marriage defines divorce as the dissolution of a marriage, this explanation can be read in Chapter VIII (dissolution of marriage and its consequences). Anyone can experience marriage and divorce, including those who have jobs as civil servants. In accordance with PP No. 45 of 1990, if a Civil Servant wants to divorce beforehand he must report and ask for permission from his superiors to carry out the divorce. But in practice, permission from superiors as a requirement for civil servant divorce is difficult to issue from superiors who wish to divorce. So that in some cases the court gave divorce decisions to Civil Servants without a letter of permission from their superiors. This is the topic of the problem that the author wants to examine in this paper. The formulation of the problem is how and what is the basis for judges in deciding divorce cases for civil servants who do not have permission from their superiors? The legal research method used is normative juridical, namely a scientific research procedure to find the truth based on the scientific logic of law from a normative perspective. The approach used is a statutory approach that relates to the main issues related to the judge's decision in civil servant divorce cases without the permission of the leadership. Legal materials in this writing use primary legal materials and secondary legal materials. From the results of the study it was concluded that the powers of the judiciary as stipulated in Law no. No. 48 of 2009 provides power and freedom for judges to decide civil servant divorce cases whose goal is to achieve justice with legal considerations and also supporting evidence, so that whether or not there is a statement of permission from superiors to divorce, is not the main guideline in determining a judge's decision